Genetic Diversity and Structure of Tropical Porites lutea Populations Highlight Their High Adaptive Potential to Environmental Changes in the South China Sea - Luo, Yanqiu; Huang, Wen; Yu, Kefu; Li, Ming; Chen, Biao; Huang, Xueyong; Qin, Zhenjun (Frontiers in Marine Science, 2022)
Global climate change and anthropogenic disturbance have significantly degraded biodiversity in coral reef ecosystems. The genetic potential and adaptability of corals are key factors used to predict the fate of global coral reefs under climate change. In this study, we used eight microsatellite loci to study the patterns of reproduction, genetic diversity, and genetic structure of 302 Porites lutea samples across 13° latitudes in the South China Sea (8.8644°N–22.6117°N). The results indicated that P. lutea reproduces largely via sexual reproduction on scales of 5 m and greater and has abundant gene diversity. Additionally, the tropical populations harbored high genetic diversity (based on alleles, effective number of alleles, gene diversity, and heterozygosity). In contrast, genetic diversity was lower in subtropical coral populations. Genetic variation values and pairwise FST revealed that tropical and subtropical populations had significantly different genetic structures. Finally, the Mantel tests showed that the genetic differentiation and genetic variation of P. lutea were strongly correlated with sea surface temperature and slightly correlated with geographical distance. These results indicated that tropical P. lutea populations have high genetic potential and adaptability because of their sexual reproduction and genetic diversity, giving them a greater capacity to cope with climate change. Subtropical coral populations showed lower genetic diversity and, thus, relatively poor genetic resilience in response to low average sea surface temperature and human activities. Our study provides a theoretical basis for the protection and restoration of coral reefs.